Anúncios de oficinas tipográficas paulistanas (1900-1930): Análise comparativa das fontes tipográficas utilizadas - Mariano Cruz Pereira, Fabio; Farias, Priscila (InfoDesign, 2021)
This article presents the results of an analysis of the typefaces used to identify São Paulo typographic workshops in advertisements published in periodicals printed during the first 3 decades of the 20th century. An answer to the following question was sought: the foundry types used to compose advertisements for a certain letterpress printing shop published in periodicals produced by other printing shops belonged to the repertoire of the company being announced, or to that of the companies that printed the periodicals? The methodological procedures involved the selection of the 20 periodicals, 49 advertisements and an analysis of movable types through overlap comparative testing. Evidence that the companies responsible for printing the periodicals were the owners of the typefaces used to announce their competitors was found.